PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA - Rainis Rainis (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is motivated by the low science learning outcomes of Class II students of SD Negeri 022 Pulau Baru Kopah. The purpose of this study is to improve student science learning outcomes by applying a direct learning model. This form of research uses classroom action research. The data needed in this study is data about the activities of teachers and students in the learning process and student learning outcomes. The data collection techniques used are observation sheets and learning outcomes tests. The results showed, seen from the total score completed on the base score of only 14 people (46.6%) while those who did not complete as many as 16 people (53.4%). After the direct learning model was carried out in the first cycle, the total students increased to 25 people (83.3%) while the incomplete students decreased to 5 people (16.4%). Cycle II, students who completed again increased to 27 people (90%) while students who did not complete became 3 people (10%). Based on these results it can be concluded that by applying the direct learning model can improve the learning outcomes of science students in grade II of SDN 022 Pulau Baru Kopah.